2015
DOI: 10.12659/msm.893138
|View full text |Cite
|
Sign up to set email alerts
|

Butorphanol and Ketamine Combined in Infusion Solutions for Patient-Controlled Analgesia Administration: A Long-Term Stability Study

Abstract: BackgroundKetamine in subanesthetic dose added to butorphanol has been reported to give superior pain control when used for intravenous patient-controlled analgesia (PCA) after surgery. However, this admixture is not available commercially and stability data applicable to hospital practice are limited.Material/MethodsThe butorphanol-ketamine admixtures were prepared in polyolefin bags and stored in the dark at 4°C, 25°C, or 37°C for 15 days. The initial concentrations were 50–150 microgram/ml for butorphanol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Combination of butorphanol tartrate with other drugs in solution has resulted in variable results. It is stable when combined with ketamine hydrochloride,8 droperidol,9 tramadol hydrochloride,18 fentanyl citrate,18 granisetron hydrochloride,19 tropisetron hydrochloride,20 perphenazine,21 and ropivacaine hydrochloride,22 but unstable with lornoxicam23 and lansoprazole24 in 0.9% sodium chloride injection. As for ketamine hydrochloride, the stability and compatibility test of ketamine hydrochloride combined with other drugs in infusion solutions has been widely demonstrated that ketamine hydrochloride is a highly stable drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of butorphanol tartrate with other drugs in solution has resulted in variable results. It is stable when combined with ketamine hydrochloride,8 droperidol,9 tramadol hydrochloride,18 fentanyl citrate,18 granisetron hydrochloride,19 tropisetron hydrochloride,20 perphenazine,21 and ropivacaine hydrochloride,22 but unstable with lornoxicam23 and lansoprazole24 in 0.9% sodium chloride injection. As for ketamine hydrochloride, the stability and compatibility test of ketamine hydrochloride combined with other drugs in infusion solutions has been widely demonstrated that ketamine hydrochloride is a highly stable drug.…”
Section: Discussionmentioning
confidence: 99%
“…Mixing two or more drugs together in infusion solutions via intravenous PCA can lead to physical and/or chemical changes, which may result in variations in therapeutic properties and unknown side effects 7. In the literature, the compatibility of butorphanol tartrate with ketamine hydrochloride or droperidol in binary admixtures was studied,8,9 but from daily practice there is a need for additional research on the compatibility of these drugs in ternary admixtures. Thus, the objective of the current study was to determine the compatibility and stability of the ternary admixture of butorphanol tartrate, ketamine hydrochloride, and droperidol in 0.9% sodium chloride injection when stored in polyolefin bags at 4°C and 25°C for 14 days.…”
Section: Introductionmentioning
confidence: 99%